2019
DOI: 10.3390/ijms20112613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Citrate Treatment in the PC3 Prostate Cancer Cell Line

Abstract: Acute administration of a high level of extracellular citrate displays an anti-proliferative effect on both in vitro and in vivo models. However, the long-term effect of citrate treatment has not been investigated yet. Here, we address this question in PC3 cells, a prostate-cancer-derived cell line. Acute administration of high levels of extracellular citrate impaired cell adhesion and inhibited the proliferation of PC3 cells, but surviving cells adapted to grow in the chronic presence of 20 mM citrate. Citrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…In this setting, an in vitro study reported the occurrence of a resistant clone of metastatic PCa cancer cells (PC3) under prolonged 10 mM citrate exposure (more than two weeks). This process was associated with a shorter PKF1 form (insensible to citrate regulation) and with the upregulation of autophagy [ 156 ]. Of note, this survival process—recycling superfluous molecules (proteins and lipids)—requires functional mitochondria for ATP production derived from FAO [ 157 ].…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…In this setting, an in vitro study reported the occurrence of a resistant clone of metastatic PCa cancer cells (PC3) under prolonged 10 mM citrate exposure (more than two weeks). This process was associated with a shorter PKF1 form (insensible to citrate regulation) and with the upregulation of autophagy [ 156 ]. Of note, this survival process—recycling superfluous molecules (proteins and lipids)—requires functional mitochondria for ATP production derived from FAO [ 157 ].…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…Lysosome distribution was quantified using Fiji software ( Caiazza et al., 2019 ). Individual cell ROIs were outlined and whole cell Lamp1 signal fluorescence was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the reprogramming strategy, the acquisition of a new phenotype passes through the modification of gene regulatory networks of the resident cell type to fit the characteristics of the incoming target cell, in terms of cell behavior, proliferation, and metabolic rate [18]. These same changes can also be associated with some pathological cellular states, like tumorigenesis [19,20]. Therefore, adequate control of somatic cell plasticity is mandatory before reprogramming could be considered a useful tool for cardiac cell therapy and tissue engineering.…”
Section: Repairing the Failing Heart With Cellular Reprogrammingmentioning
confidence: 99%